HUBUNGAN ANTARA PENGETAHUAN TEORI DAN KEMAMPUAN PRAKTIK MATA PELAJARAN SISTEM KELISTRIKAN DENGAN MINAT MELANJUTKAN STUDI SISWA KELAS XI SMK PIRI SLEMAN PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN TAHUN 2015/2016 - Awaludin Awaludin; Samidjo Samidjo (Universitas Sarjanawiyata Tamansiswa, 2016)
The study aimed to describe (1) correlation between theory knowledge with interest to continue the study; (2) correlation between practice competence of electrical system subject with interest to continue the study; and (3) correlation between theory knowledge and practice competence of electrical system subject with interest to continue the study among the eleventh grade students of vocational school Piri Sleman in academic year 2014/2015. This study was ex-post facto research. Data collecting methods were questionnaires and documentation. Data analyzing methods used descriptive analysis, first and second hypothesis testing used partial correlation and third hypothesis testing used double regression. This study shows that (1) there was a positive and significant correlation between theory knowledge with learning achievement of among the eleventh grade students of vocational school Piri Slemanin academic year 2015/2016 with the significant score 0.000 < 0.05; (2) there was a positive and significant correlation between practice competence of electrical system subject with interest to continue the study among the eleventh grade students of vocational school Piri Slemanin academic year 2015/2016 with the significant score 0.000 < 0.05; and (3) there was a positive and significant correlation between theory knowledge and practice competence of electrical system subject with interest to continue the study among the eleventh grade students of vocational school Piri Sleman in academic year 2015/2016 with the significant score 0.000 < 0.05. The score of determinant coefficient (R2) 0.323, it means that theory knowledge and practice competence of electrical system subject gave a positive contribution 32.3% toward interest to continue the study, while 67.7% was influenced by other factors that were not discussed in this study